Evaluation of the colour change in enamel and dentine promoted by the interaction between 2% chlorhexidine and auxiliary chemical solutions. (29th May 2011) - Souza, Matheus; Cecchin, Doglas; Barbizam, Joao V.B.; Almeida, José F.A.; Zaia, Alexandre Augusto; Gomes, Brenda P.F.A.; Ferraz, Caio C.R.
Abstract To evaluate the colour change in enamel and dentine, promoted by interaction of 2% chlorhexidine gluconate (CHX) with 5.25% sodium hypochlorite (NaOCl) and 17% ethylenediaminetetraacetic acid (EDTA). Fragments containing enamel and dentine were obtained from the crowns of extracted bovine incisors. Before and after immersion of the samples in the substances, they were evaluated with reference to the colour of the enamel and dentine. The values obtained in numerical scores were subjected to statistical analysis using Wilcoxon test. A colour change in the enamel and dentine in groups treated with CHX gel + NaOCl and CHX gel + NaOCl + EDTA, and a change in colour only in the dentine in groups treated with CHX solution + NaOCl and CHX solution + NaOCl + EDTA. When used prior to NaOCl, CHX has the ability to induce a colour change in dental structures.